The Effect of Commercial Genetic Selection on Somatotropic Gene Expression in Broilers: A Potential Role for Insulin-Like Growth Factor Binding Proteins in Regulating Broiler Growth and Body Composition - Vaccaro, Lauren A.; Porter, Tom E.; Ellestad, Laura E. (Frontiers in Physiology, 2022)
The somatotropic axis influences growth and metabolism, and many of its effects are a result of insulin-like growth factor (IGF) signaling modulated by IGF-binding proteins (IGFBPs). Modern commercial meat-type (broiler) chickens exhibit rapid and efficient growth and muscle accretion resulting from decades of commercial genetic selection, and it is not known how alterations in the IGF system has contributed to these improvements. To determine the effect of commercial genetic selection on somatotropic axis activity, two experiments were conducted comparing legacy Athens Canadian Random Bred and modern Ross 308 male broiler lines, one between embryonic days 10 and 18 and the second between post-hatch days 10 and 40. Gene expression was evaluated in liver and breast muscle (pectoralis major) and circulating hormone concentrations were measured post-hatch. During embryogenesis, no differences in IGF expression were found that corresponded with difference in body weight between the lines beginning on embryonic day 14. While hepatic IGF expression and circulating IGF did not differ between the lines post-hatch, expression of both IGF1 and IGF2 mRNA was greater in breast muscle of modern broilers. Differential expression of select IGFBPs suggests their action is dependent on developmental stage and site of production. Hepatic IGFBP1 appears to promote embryonic growth but inhibit post-hatch growth at select ages. Results suggest that local IGFBP4 may prevent breast muscle growth during embryogenesis but promote it after hatch. Post-hatch, IGFBP2 produced in liver appears to inhibit body growth, but IGFBP2 produced locally in breast muscle facilitates development of this tissue. The opposite appears true for IGFBP3, which seems to promote overall body growth when produced in liver and restrict breast muscle growth when produced locally. Results presented here suggest that paracrine IGF signaling in breast muscle may contribute to overall growth and muscle accretion in chickens, and that this activity is regulated in developmentally distinct and tissue-specific contexts through combinatorial action of IGFBPs.